The Implementation of Role Models in Students’ Writing Descriptive Text in SMKN 1 Kab.Wajo - Nur Fadilah; Syarifuddin Dollah; Maemuna Muhayyang (State University of Makassar, 2023)
This research is pre-experimental in one-group-pretest-postest design that aimed to find out whether or not the implementation of role models improved the students' descriptive writing skills in SMKN 1 KAB. Wajo and students’ interest. The sample of this research is 23 students of a class at the ten grade students in SMKN 1 KAB. WAJO in academic year 2021/2022. To get data, the researcher gives a pre-test before the treatment. The treatment that has been given to students is to explain material regarding descriptive text in 4 meetings, the researcher explains the components of writing, explains what role models are, and several types of role models. Thus treatment result can be known to be more accurate because it can compare the condition before given the treatment. After that, the data are analysed using SPSS 25.0. The result showed that the students descriptive writing text for X AKL students of SMK Negeri 1 Wajo before applying the treatment (pre-test) are categorized as very poor with an mean score of 76,96. Meanwhile, the results of students descriptive writing test for class X students of SMK Negeri 1 Wajo after applying the Treatment (post-test) were categorized as quite good with an mean score of 85,61. Moreover, the results of students interest for X AKL students of SMK Negeri 1 Wajo before applying the treatment (pre-test) are categorized as very poor with an mean score of 70,65. Meanwhile, the results of students descriptive writing test for class X students of SMK Negeri 1 Wajo after applying the Treatment (post-test) were categorized as quite good with an mean score of 84,74. It can be proven by the hypothesis value was lower than P (0.000 ˂ 0.05) which means (H1) was accepted. Therefore, it is concluded that role models improve the writing skill of the eleventh-grade students of SMK Negeri 1 Wajo. Keywords— role model, descriptive text, writing skill